Nitrous oxide-induced neurotoxicity: Clinical characteristics and impacts on overall neurological impairments - Gao, Hui; Wang, Ruihan; Zeng, Yan; Qin, Linyuan; Cai, Hanlin; Zhou, Dong; Chen, Qin (Frontiers in Neurology, 2023)
Objective: The reports of the recreational use of nitrous oxide (N2O) and its related neuropathy are increasing. However, it is unclear whether specific clinical characteristics are associated with the overall neurological impairments among these individuals. Methods: We retrospectively included 20 hospitalized patients with N2O-related neurological complaints between January 2016 and March 2021 at West China Hospital, Sichuan University. Detailed demographic, clinical features, lab tests, and imaging data were collected. A functional disability rating score (FDRS) was calculated to determine the degree of neurological impairment. The relationships between the above factors and the FDRS sum score were explored. Results: These individuals were aged between 16 and 30 (mean ± SD: 21.90 ± 4.06). At admission, unsteady gait (95%, 19/20), weakness (95%,19/20), and limb paresthesia (70%,14/20) were the most common symptoms; decreased deep tendon reflexes (100%, 19/19), reduced muscle strength (95%, 19/20), and impaired coordination (95%, 19/20) were frequently found. The FDRS sum scores ranged from 3 to 12. Among all the factors, admission from the emergency room (p=0.033), decreased hemoglobin (p=0.004) (without previous VitB12 supplements), decreased red blood cell (RBC) count (p=0.004) (without previous VitB12 supplements), and increased mean corpuscular volume (p=0.036) (with previous VitB12 supplements) positively correlated with the FDRS sum score. Conclusion: N2O could lead to severe neurological impairments among users. Abnormal RBC indicators at admission may be associated with a worse clinical presentation and need further attention. Population education about the consequences of N2O consumption and control measures concerning access to N2O should be further emphasized.